2011
DOI: 10.3109/0886022x.2011.605536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Omega-3 Fatty Acids on Serum Lipids, Lipoprotein (a), and Hematologic Factors in Hemodialysis Patients

Abstract: Background: Lipid abnormalities, especially high serum lipoprotein (a) [Lp (a)] concentration, and anemia are two major causes of cardiovascular diseases (CVDs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 32 publications
(47 reference statements)
8
36
1
1
Order By: Relevance
“…There are no similar or comparable reports in dogs in the literature. In humans, there are reports of haemoglobin reduction in healthy individuals [96] and no change in patients with risk of anaemia after supplementation with fish oil [97, 98]. Likewise, we observed a significant reduction of the MCV values within the fish oil group, but comparable changes in dogs were not found elsewhere; also, no statistical difference was observed between groups.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There are no similar or comparable reports in dogs in the literature. In humans, there are reports of haemoglobin reduction in healthy individuals [96] and no change in patients with risk of anaemia after supplementation with fish oil [97, 98]. Likewise, we observed a significant reduction of the MCV values within the fish oil group, but comparable changes in dogs were not found elsewhere; also, no statistical difference was observed between groups.…”
Section: Discussionsupporting
confidence: 75%
“…Likewise, we observed a significant reduction of the MCV values within the fish oil group, but comparable changes in dogs were not found elsewhere; also, no statistical difference was observed between groups. Elevations in packed cell volume after ingestion of fish oil for six weeks have been reported in healthy human beings [96], and no difference were found in patients with risk of anaemia [97]. The leucocyte counts of dogs in the present study revealed a significant reduction in the number of monocytes and basophils in the group receiving fish oil, from baseline to the end of the trial.…”
Section: Discussionsupporting
confidence: 47%
“…Clinical studies have demonstrated that DHA supplementation has no effect on iron absorption [28,32] that is in agreement with the results of the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Fasting serum ferritin was measured by chemiluminescent immunoassay (CLIA, Liaison, DiaSorin, Italy); serum ApoA-I and ApoB were measured by turbidimetry (Cobas Integra 400, Roche Diagnostics, Mannheim, Germany) [28]; serum iron was measured by spectrophotometer based on the reaction of iron with ferene reagent at acidic conditions, and hs-CRP was measured by immunofluorescence (Vitros Chemistry Products, Johnson & Johnson Clinical Diagnostics, Rochester, USA) [29]. Paraoxonase-1 was measured by spectrophotometry [30].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…45% irrespective of the plasma concentration of Lp(a) [111]. This is in agreement with many other studies showing that fish oils only seem to be able to reduce Lp(a) in combination with other therapies [107] or moderate exercise [112] but not when used alone [113,114,115].…”
Section: Lp(a) and Lipid Lowering Drugssupporting
confidence: 80%